The Khutub Khanah - Hamdan Yusi, Atiqah Al-Insyirah; Ahmad, Masitah; Ismail, Saidatul Akmar; Jamil, Nurul Izzah; Rahmat, Nur Rawaidah (2025)
The Khutub Khanah (TKK) is an innovative AI platform that is built to locate and centralize access to a selection of reliable AI websites that are suitable for educational purposes. In the current digital landscape, AI tools are being developed rapidly, and there are tons of AI websites that are growing in number and complexity. It is an advantage to use AI for learning purposes; it can create interactive learning and can be used as a guide for learning purposes. However, it can be overwhelming to identify an AI platform that is not effective and age-appropriate for learning, other as an ethical issue that needs to be considered while using AI. TKK addresses this gap by offering a curated hub that is safe and relevant for users with different learning levels. Recognizing the potential of AI in transforming education, TKK comes by using the technology to support an interactive learning experience and explore the ethical implications and responsibilities associated with the use of AI. TKK is created to support 3 categories of learners for their learning purposes. These 3 groups are researchers, school students, and young children. For researchers, it provides access to AI tools that support research activities. TKK offers school students to enhance their understanding of core subjects and guide them with their homework. For children, it will be a safe and fun AI-based education tool to promote early literacy. TKK makes AI tools more accessible, structured, and safe for smart education across all age groups.